Morphological characteristics of terminalia of the wasp-mimicking fly, Stomorhina discolor (Fabricius) - Kittikhun Moophayak (2018)
© 2017 by the authors; licensee MDPI, Basel, Switzerland. Stomorhina discolor (Fabricius), a species of blow fly that mimics wasps, is distributed worldwide, but detailed information about characteristics of its adult terminalia is incomplete. To help fill this gap in the information, the morphology of adult stages of S. discolor was investigated using light microscopy and scanning electron microscopy. Observations using the light microscope revealed unique characteristics of the male genitalia that are markedly different from other blow fly species. More morphological detail, including observation of several sensilla (e.g., sensilla trichoid and sensilla basiconica) along the male terminalia and female ovipositor, was seen under the scanning electron microscope. These details can be taxonomically valuable for identifying males and females of S. discolor and may help address matters concerning copulation in this species.